2015
DOI: 10.4085/1062-6050-50.5.09
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Athletic Trainer's Role in Assisting Student-Athletes Presenting With Alcohol-Related Unintentional Injuries

Abstract: Compared with their nonathlete peers, collegiate athletes consume higher quantities of alcohol, drink with greater frequency, and exhibit an increased propensity to engage in heavy episodic drinking (ie, binge drinking), which often may result in alcohol-related consequences. Moreover, collegiate athletes are also more likely to engage in other maladaptive lifestyle behaviors, such as participating in physical fights and riding with an intoxicated driver, and less likely to engage in protective behaviors, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…2 As such, ATs play a critical role in the promotion of safe physical activity and return to participation after injury. Furthermore, the National Athletic Trainers' Association (NATA) position statements and bestpractice documents require ATs to be educated on, and assist in, preventing or otherwise managing orthopaedic injuries, [3][4][5] concussions, 6 eating disorders, 7 heat illnesses, 8 lightning injuries, 9 cardiac-related deaths, 10 diabetic episodes, 11 exertional sickling episodes, 12 early-onset osteoarthritis, 13 substance abuse, 14 disease transmission, 15 weight management, 16 and dental and oral injuries 17 in their scope of practice using evidence-based techniques. These prevention mechanisms are common practice for ATs and well within their scope of practice; however, many secondary schools that do not provide on-site AT services are left to implement these measures through other means.…”
mentioning
confidence: 99%
“…2 As such, ATs play a critical role in the promotion of safe physical activity and return to participation after injury. Furthermore, the National Athletic Trainers' Association (NATA) position statements and bestpractice documents require ATs to be educated on, and assist in, preventing or otherwise managing orthopaedic injuries, [3][4][5] concussions, 6 eating disorders, 7 heat illnesses, 8 lightning injuries, 9 cardiac-related deaths, 10 diabetic episodes, 11 exertional sickling episodes, 12 early-onset osteoarthritis, 13 substance abuse, 14 disease transmission, 15 weight management, 16 and dental and oral injuries 17 in their scope of practice using evidence-based techniques. These prevention mechanisms are common practice for ATs and well within their scope of practice; however, many secondary schools that do not provide on-site AT services are left to implement these measures through other means.…”
mentioning
confidence: 99%
“…An analogous inclination was noted in American studies. the consumption of alcoholic beverages was higher in students of athletic fields than in their colleagues studying other subjects [19,20]. A great popularity of drinking was additionally documented in the case of French students of sports-related majors [5].…”
Section: Discussionmentioning
confidence: 89%
“…To the best of our knowledge, no study to date reported associations between alcohol consumption and injury, which is surprising mostly due to two reasons. First, previous reports evidenced disturbing prevalence of alcohol consumption in ballet; and second, drinking is related to injury status in physically demanding professions, such as sports and the army [ 20 , 38 ]. Therefore, our results of the negative influence of alcohol consumption on recovery from injury in ballet are pioneering to some extent, and a brief overview of the physiological mechanisms that generate such associations is provided.…”
Section: Discussionmentioning
confidence: 99%